Analysis of the Implementation of Electronic Medical Records in Efficiency, Productivity, and Performance of Health Services at the Sriamur Bekasi Health Center with the Wellbeing Method - W.D, Himas; Ria Rajagukguk, Jenni; Muktiono, Ayub (International Journal of Engineering, Science and Information Technology, 2024)
The application of digital technology in health services has significantly improved efficiency and service quality. Electronic Medical Record (E.M.R.) is a technology implementation that records, stores, and manages patient medical data electronically. This study aims to analyze the impact of using E.M.R. on the productivity and efficiency of health services at the Sriamur Bekasi Community Health Center. This research uses the Wellbeing method with a qualitative approach. Primary data was collected through in-depth interviews and questionnaires distributed to the medical and administrative staff of the Sriamur Community Health Center. Secondary data on the number of patients before and after E.M.R. implementation was also analyzed. The leading indicators measured include service time, quality, error rate, and human resource utilization. The research results show a significant increase in productivity and efficiency after E.M.R. implementation. The number of patients served per day increases, and the time required for recording and retrieving patient data is reduced. Respondents indicated high satisfaction with using E.M.R., with the majority assessing that the system helps speed up administrative processes and improve the accuracy of medical data. Implementing E.M.R. at the Sriamur Bekasi Community Health Center has increased the medical staff's operational efficiency and productivity. This technology makes it easier to access and manage patient data and reduces the administrative burden so that medical personnel can focus more on health services. To maximize the benefits of E.M.R., ongoing training and regular evaluation of existing systems and procedures are required.